(untitled) (Journal of the Sociology and Theory of Religion, 2020)
The legal and political concept of church-state separation is one of the measures established in secular states, including the economy. The separation does not exist in countries governed by Islamic law, called sharia. An aspect of current affairs is the appearance of cryptocurrencies and their questioning due to their speculative nature: halal or haram? It is an aspect of current affairs among regulators, central banks and authorities. One possible solution with compliance with muslim precepts is the OneGram (OGC), which was recognized as the best Islamic financial product of 2018 at the Global Islamic Finance Awards.